Heterobasidion Infection in Abies nordmanniana ssp. bornmulleriana Stands in Kastamonu Province - Lehtijarvi, A.; Dogmus-Lehtijarvi, H. T.; Unal, S.; Karadeniz, M.; Kaya, A. G. Aday; Oskay, F. (Kastamonu Univ, Orman Fak, 2012)
In this study, the proportion of Abies bornmulleriana trees infected by Heterobasidion spp. was investigated in Kastamonu Province in different types of stands. One 1 cm-thick disc was taken from each of 100 freshly cut trees, washed under a running tap, placed into plastic bags and incubated in growth chamber at 24 C degrees for 7 days. The area occupied by the conidial stage of Heterobasidion annosum s. l. was determined under a stereomicroscope using transparent film placed onto the upper surface of each disc. During this investigation conidia of Heterobasidion annosum s. l. were taken with a needle and placed onto agar plates. The obtained isolates were identified with pairing tests and DNA-based methods. All 36 isolates responded as Heterobasidion abietinum to the tester isolates. Identification based on PCR amplification with MJF - MJR and KJF-KFR primers gave the same result. 34% (34 out of 100) of the discs taken from the fir forests were found to be infected with H. abietinum. The characteristics of the colonized patches on the discs indicated that the H. abietinum colonies originated from stem infections of the trees. The proportion of the disc area covered by the conidial stage of the fungus was 80% in one of the discs, 6-10% in 6 discs, 1-5% in 18 discs, and 0-1 % in 11 discs. The conidiophores were observed in heartwood in only five samples.
Keywords: Abies bornmulleriana; Fir Stands; Heterobasidion